Enhancing Engineering Competencies through Sustainable Design: A Project- and Problem-Based Learning Approach for Industrial Engineering Students - Castaño Reyes, Carmen Elizabeth; Bernal Mojica, Bolivar; Noguera Cardoza, Juan Carlos; Chen Austin, Miguel; Ortega Del Rosario, Maria De Los Angeles; Caballero, Ricardo (LACCEI, 2024)
In contemporary engineering education, the conventional subject-focused structure often falls short in fostering the necessary problem- and project-based approaches to build necessary competencies. This paper proposes a five-subject modular concept integrating different departments to develop transdisciplinary skills without compromising on content. It links different modern teaching methods to test their eight students’ interaction potential and productivity. This proposed concept encourages collaborative supervision by professors from diverse higher education centers, challenging students to participate in a semester-long simulation where two groups emulate start-up companies. Tasked with competing in planning, designing and developing a sustainable solution from plastic waste (HDPE), students delve into hands-on experiences, learning how to integrate the requirements and approaches of sustainable production. During the module, knowledge and fundamental skills in the field of engineering were qualitatively measured before and after to compare with the skills learned through the module.